Eocene bipolar glaciation associated with global carbon cycle changes - Tripati, A.; Backman, J.; Elderfield, H.; Ferretti, P. (Nature, 2005)
The transition from the extreme global warmth of the early Eocene 'greenhouse' climate similar to 55 million years ago to the present glaciated state is one of the most prominent changes in Earth's climatic evolution. It is widely accepted that large ice sheets first appeared on Antarctica similar to 34 million years ago, coincident with decreasing atmospheric carbon dioxide concentrations and a deepening of the calcite compensation depth in the world's oceans, and that glaciation in the Northern Hemisphere began much later, between 10 and 6 million years ago. Here we present records of sediment and foraminiferal geochemistry covering the greenhouse - icehouse climate transition. We report evidence for synchronous deepening and subsequent oscillations in the calcite compensation depth in the tropical Pacific and South Atlantic oceans from similar to 42 million years ago, with a permanent deepening 34 million years ago. The most prominent variations in the calcite compensation depth coincide with changes in seawater oxygen isotope ratios of up to 1.5 per mil, suggesting a lowering of global sea level through significant storage of ice in both hemispheres by at least 100 to 125 metres. Variations in benthic carbon isotope ratios of up to similar to 1.4 per mil occurred at the same time, indicating large changes in carbon cycling. We suggest that the greenhouse - icehouse transition was closely coupled to the evolution of atmospheric carbon dioxide, and that negative carbon cycle feedbacks may have prevented the permanent establishment of large ice sheets earlier than 34 million years ago.